New methods for quantification of amoxicillin and clindamycin in human plasma using HPLC with UV detection. (23rd June 2022) - Greibe, Eva; Moser, Claus Ernst; Bruun, Niels Eske; Hoffmann-Lücke, Elke
Abstract: Objectives: We aimed to develop simple and rapid HPLC methods for determination of amoxicillin and clindamycin in human plasma. Methods: Plasma samples were pretreated by direct deproteinization with acetonitrile and the analytical separation took place on a reverse phase Poroshell 120 EC-C18 column (2.7 μm, 2.1  ×  100 mm) with a gradient of acetonitrile. UV detection at 229 nm for amoxicillin and 204 nm for clindamycin was used for determination of the antibiotics in plasma. Results: The calibration curves were linear over the concentration ranges of 1–100 mg/L for amoxicillin and 1–15 mg/L for clindamycin with a correlation coefficient of ≥0.98. Intra-assay precisions were all ≤15% and the accuracies were within ±15%. The limit of quantification (LOQ) was found to be 0.5 mg/L for amoxicillin and 1 mg/L for clindamycin with inter-assay imprecision coefficient of variances (CVs) of 18.7% and 15.6%, respectively. The present HPLC methods were successfully applied on spike-in samples and on plasma samples collected 4–6 and 3.5–5.5 h after oral antibiotic administration of 500 mg of amoxicillin and 600 mg of clindamycin, respectively. Conclusions: We have developed HPLC methods with UV detection for quantification of amoxicillin and clindamycin in human plasma. The methods are fast, simple and suitable for use in routine settings and clinical studies.